2016
DOI: 10.1111/liv.13288
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sofosbuvir/simeprevir plus flat dose ribavirin in genotype 1 elderly cirrhotic patients: A real‐life study

Abstract: Sofosbuvir/simeprevir plus a daily flat dose of RBV 800 mg for 12 weeks was highly effective and safe in genotype 1 elderly patients with compensated cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…In our study, overall SVR rates (96%) were comparable to those reported in registration trials [2,3] and real-life studies [5,6,[8][9][10][11][12][13], and were independent of baseline renal function, as previously reported [11,12,19,33]. Interestingly, the highest SVR rates were achieved by those treated with SOF-free (p = 0.0003) and RBV-free (p = 0.0017) combinations.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, overall SVR rates (96%) were comparable to those reported in registration trials [2,3] and real-life studies [5,6,[8][9][10][11][12][13], and were independent of baseline renal function, as previously reported [11,12,19,33]. Interestingly, the highest SVR rates were achieved by those treated with SOF-free (p = 0.0003) and RBV-free (p = 0.0017) combinations.…”
Section: Discussionsupporting
confidence: 89%
“…A second explanation for the good results obtained in our cohort is the lower prevalence of GT1a‐infected patients in Spain, and the reduced European prevalence of Q80K mutation in GT1a compared to USA . Although the negative impact of Q80K resistant‐associated substitution (RAS) in GT1a patients undergoing SOF/SMV is not as evident as in those treated with PR plus SMV, SVR rates were lower in patients harbouring this RAS both in the COSMOS and OPTIMIST‐II trials. This is in line with the reduced SVR rates observed in patients previously exposed to a protease‐inhibitor as part of triple therapy.…”
Section: Discussionmentioning
confidence: 78%
“…Although no differences in efficacy were described between those receiving RBV or not (91% vs 96%), patients treated with RBV presented a more advanced liver disease, probably impacting global results. Another multicentric study including 270 GT1 compensated cirrhotics treated for 12 weeks with SOF/SMV plus RBV reported excellent efficacy (SVR 95.9%) and tolerability (<2% SAE,<6% discontinuation). On the other hand, supporting the usefulness of RBV in cirrhotic patients, the OPTIMIST 2 phase‐III trial reported efficacy rates of only 83% in a cohort of 103 compensated cirrhotic patients treated for 12 weeks with SOF/SMV without RBV.…”
Section: Discussionmentioning
confidence: 97%
“…SVR rates were lower in presence of cirrhosis compared to non-cirrhotic patients (87% vs 98% with SOF/DCV [ 17 ] and 81% vs 91% with SOF/SIM [ 26 ]. Higher SVR rates can be achieved in cirrhotic patients when extending SOF/DCV for 24 weeks [ 17 ] or adding RBV to SIM/SOF [ 24 ]. Pol et al reported lower SVR rates in GT1a patients compared to GT1b (89% vs 95% with SOF/DCV 12 weeks) that might be not significant when extending treatment for 24 weeks (95% for both) [ 17 ].…”
Section: Resultsmentioning
confidence: 99%